Estimating production functions and technical change from micro data : An exploratory study of individual establishment time-series from Norwegian mining and manufacturing 1959-1967 - Ringstad, Vidar (Oslo : (Aschehoug), 1971)
This study is of an explanatory nature where a variety of problems concerning the estimation of production function parameters and technical change are considered.
Title also in Norwegian: Estimering av produktfunksjoner og tekniske endringer fra mikro data.
Summary in Norwegian.
Bibliography: p. 222-224.
osc 16/10/2018
Loans
Keywords: Line of balance (Management); Industries